A new anti-mesothelin antibody targets selectively the membrane-associated form. Issue 3 (3rd April 2017) - Asgarov, Kamal; Balland, Jeremy; Tirole, Charline; Bouard, Adeline; Mougey, Virginie; Ramos, Diana; Barroso, António; Zangiacomi, Vincent; Jary, Marine; Kim, Stefano; Gonzalez-Pajuelo, Maria; Royer, Bernard; et al.
ABSTRACT: Mesothelin is a glycosylphosphatidylinositol (GPI)-anchored membrane protein that shows promise as a target for antibody-directed cancer therapy. High levels of soluble forms of the antigen represent a barrier to directing therapy to cellular targets. The ability to develop antibodies that can selectively discriminate between membrane-bound and soluble conformations of a specific protein, and thus target only the membrane-associated antigen, is a substantive issue. We show that use of a tolerance protocol provides a route to such discrimination. Mice were tolerized with soluble mesothelin and a second round of immunizations was performed using mesothelin transfected P815 cells. RNA extracted from splenocytes was used in phage display to obtain mesothelin-specific antigen-binding fragments (Fabs) that were subsequently screened by flow cytometry and ELISA. This approach generated 147 different Fabs in 34 VH-CDR3 families. Utilizing competition assays with soluble protein and mesothelin-containing serum obtained from metastatic cancer patients, 10 of these 34 VH-CDR3 families were found to bind exclusively to the membrane-associated form of mesothelin. Epitope mapping performed for the 1H7 clone showed that it does not recognize GPI anchor. VH-CDR3 sequence analysis of all Fabs showed significant differences between Fabs selective for the membrane-associated form of the antigen and those that recognize both membrane bound and soluble forms. This work demonstrates the potential to generate an antibody specific to the membrane-bound form of mesothelin. 1H7 offers potential for therapeutic application against mesothelin-bearing tumors, which would be largely unaffected by the presence of the soluble antigen.